A Colour Code Algorithm For Signature Recognition - Kulkarni, Vinayak B. (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2007)
The paper "A Colour Code Algorithm for Signature Recognition" accounts an image processing application where any user can verify signature instantly. The system deals with a Colour code algorithm, which is used to recognize the signature. The paper deals with the recognition of the signature, as human operator generally make the work of signature recognition. Hence the algorithm simulates human behavior, to achieve perfection and skill through AI. The logic that decides the extent of validity of the signature must implement Artificial Intelligence Pattern recognition is the science that concerns the description or classification of measurements, usually based on underlying model. The measurement or the properties used to classify the objects are called as 'features', and the types or categories into which they are classified are called as classes. Since most pattern recognition tasks are first done by humans and automated later, the most fruitful source of features has been to asked the people who classify the objects how they tell them a part. The two main approaches to pattern recognition are the statistical (decision theoretic) and the syntactic approaches. Signature recognition is the best example of this fact. The algorithm is tested on various operating systems & we find that it works very well & satisfactory. While implementing the recognition process, we have used quite simpler way. At this stage we are getting accuracy up to about 80% to 90%. These conclusions are made on the basis of testing of 300 person's database.